Using the Concerns Based Adoption Model (CBAM) to Evaluate Teachers’ Concerns About the CAC in Three (3) Primary Schools in the Caroni Education District - Ramoutar-Bhawan, Ancyia (My University, 2014)
Employing the Concerns Based Adoption Model (CBAM) as its theoretical framework, this study evaluated the concerns of six teachers at three primary schools in the Caroni Educational District of Trinidad and Tobago about the Continuous Assessment Component (CAC) of the Secondary Entrance Assessment (SEA) examination. Data were collected through interviews. The major findings of the study indicated that the teachers’ most intense concerns were in the awareness, informational, personal, and management stages of concerns. They had deep self-concerns (need for information on training, support systems, school policy for CAC) and task concerns (time management, resource allocation, management of assessment system).
Keywords: Concerns; Primary school teachers; Teacher attitudes; Continuous Assessment Component; Secondary Entrance Assessment examination; Case studies; Curriculum implementation; Primary school curriculum; Trinidad and Tobago